2006
DOI: 10.1089/jam.2006.19.392
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized In Vitro Model of the Respiratory Tract Wall to Study Particle Cell Interactions

Abstract: As a part of the respiratory tissue barrier, lung epithelial cells play an important role against the penetration of the body by inhaled particulate foreign materials. In most cell culture models, which are designed to study particle-cell interactions, the cells are immersed in medium. This does not reflect the physiological condition of lung epithelial cells which are exposed to air, separated from it only by a very thin liquid lining layer with a surfactant film at the air-liquid interface. In this study, A5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(161 citation statements)
references
References 40 publications
3
156
0
2
Order By: Relevance
“…This results in the formation of multilayers, a known phenomenon during an extended culturing period at the air−liquid interface (>24 h postexposure; Figure 2 and Supporting Information, Figure 4). 45 The confocal images in Figure 2 show the distribution of the CNCs deposited, via the ALICE, after nebulization. Individual fibers cannot be spatially resolved due to the resolution limit of sub-100 nm objects, only fiber bundles/aggregates are visible by LSM.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in the formation of multilayers, a known phenomenon during an extended culturing period at the air−liquid interface (>24 h postexposure; Figure 2 and Supporting Information, Figure 4). 45 The confocal images in Figure 2 show the distribution of the CNCs deposited, via the ALICE, after nebulization. Individual fibers cannot be spatially resolved due to the resolution limit of sub-100 nm objects, only fiber bundles/aggregates are visible by LSM.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Exposure in the "Air Liquid Interface Cell Exposure System" (ALICE). All in vitro experiments were performed with a coculture model of the epithelial airway barrier of the human lung, 45,46 as detailed by Lehmann et al 47 Additionally, the selection of CD14 + cells was employed, as further described by Steiner et al 48 The aerosolization of nanoparticles with the ALICE system was previously published 41 and recently applied to HARN with the example of unmodified CNCs.…”
Section: 41mentioning
confidence: 99%
“…Cocultures were prepared as previously described. 15,49 Briefly, adenocarcinoma human alveolar basal epithelial cells (A549 cells) were grown under submerged conditions for 5 days on cell culture inserts (surface area of 4.2 cm 2 , pores with 3.0 μm diameter, high pore density PET membranes for six-well plates (BD Biosciences, Basel, Switzerland; 353502) at a density of 1 × 10 6 cells/mL). Monocytes were isolated from human buffy coat from healthy volunteers (Blood Donation Service, Bern University Hospital, Bern, Switzerland) by gradient centrifugation (Lymphoprep, Axis Scield, Oslo, Norway) as previously described by Blank et al 9 and Fytianos et al 13 Monocytes were differentiated into MDDCs by adding 10 ng/mL granulocyte−monocyte−colony stimulating factor and 10 ng/mL IL-4.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that nanoparticle translocation into capillaries leads to their translocation into other organs [60][61][62][63][64][65], and evidence is emerging that the route of entry, and the biomolecules that form the initial corona at the site of entry (e.g., plasma proteins following injections versus lung surfactant proteins following inhalation), play a distinct role in determining the organ biodistribution of nanoparticles [66]. For example, accumulation of TiO 2 nanoparticles in the brain was 100-fold higher for particles entering via lung than for those injected directly into the bloodstream (Personnal Communication W.G.…”
Section: The Translocation Concept: Interactions Of Nanomaterials Witmentioning
confidence: 99%